(untitled) (Research, Society and Development, 2022)
Objective: To analyze and address the causes and alterations related to hyperalphalipoproteinemia, comparing the general patterns of the population. Methodology: An Integrative Literature Review was conducted, in which key words specified in the Pubmed and Science Direct databases were used: "hyperalphalipoprotenemia" OUR "hyperalphalipoprotein" OUR "HDLc". Results: Mutations in individuals with hyperalphalipoproteinemia, single nucleotide polymorphisms, deleterious genes, cetp gene, hepatic SR-BI, endothelial lipase (EL) gene, splicing defect, genes and proteins ANGPTL3 and ANGPTL8 can be highlighted. In addition, changes in surface fluidity and HDLc membrane constituents were noted, changes in the RCT process and in the ability to increase expression and to activate endothelial synthesis of nitric oxide (NO). Furthermore, changes caused by CETP deficiency cannot be related to a cardioprotective, antiatherogenic and anti-inflammatory effect, and even a U-shaped relationship between plasma HDLc and ischemic electrocardiographic changes, where CETP deficiency accumulates. Moreover, the presence of the P376L variant, intervenenegatively in the processing of SR-BI. Finally, individuals with higher HDLc levels exhibit cholesterol particles enriched by apolipoproteins, which cause changes to the anti-inflammatory action of HDL itself. Conclusion: Changes in the physiological functioning of HDLc, which cause hyperalphalipoproteinemia, are caused by several mutations that lead to changes in the membrane mechanism, CETP, SR-BI and inflammatory processes. More research is needed to conclude about the cardioprotective effect.